High glucose induces pyroptosis of retinal microglia through NLPR3 inflammasome signaling - Huang,Libin (2021)
ABSTRACT Purpose: Diabetic retinopathy is currently considered a chronic inflammatory disease involving NOD-like receptor family pyrin domain containing 3 inflammasome activation and retinal microglial pyroptosis. In this study, we aimed to investigate whether NOD-like receptor family pyrin domain containing 3 inflammasome signaling induces pyroptotic death of retinal microglia under high-glucose conditions. Methods: Retinal microglia were stimulated by high glucose levels for 24 h. Cell viability, lactate dehydrogenase release, and caspase-1 activity were detected in vitro. The expression of pro-inflammatory cytokine (interleukin-1β, activated microglia marker ionized calcium-binding adapter molecule-1), NOD-like receptor family pyrin domain containing 3, cleaved caspase-1, and cleaved gasdermin D were examined. Subsequently, retinal microglia were pretreated with the inhibitors of NOD-like receptor family pyrin domain containing 3 inflammasome signaling prior to stimulation with high glucose, and their molecular and functional changes were evaluated. Results: High-glucose (25, 50, or 100 mM) stimulation decreased cell viability, but enhanced lactate dehydrogenase release and caspase-1 activity in a dose-dependent manner. Moreover, high glucose upregulated the protein expression of interleukin-1β, ionized calcium-binding adapter molecule-1, NOD-like receptor family pyrin domain containing 3, cleaved caspase-1, and cleaved gasdermin D. However, pretreatment with the inhibitors of NOD-like receptor family pyrin domain containing 3 inflammasome signaling inhibited high glucose (25 mM)-induced cytotoxicity, NOD-like receptor family pyrin domain containing 3 inflammasome activation, and pyroptosis of retinal microglia. Conclusions: NOD-like receptor family pyrin domain containing 3 inflammasome signaling may modulate retinal microglia-related inflammation and pyroptosis under high-glucose conditions.